PEMANFAATAN LIMBAH KULIT BUAH-BUAHAN SEBAGAI ECO-ENZYME DI PANTI ASUHAN PUTRI AISYIYAH PUCANG GADING - Larasaty, Nurina Dyah; Astuti, Andari Puji; Miranti, Apni (Gapenas Publisher, 2025)
Putri Aisyiyah Orphanage Pucang Gading is an orphanage that houses orphaned girls. The environmental health problem at the orphanage is the large amount of garbage that has been piled up for days, causing an unpleasant odor because there are no garbage collectors willing to pick up trash at the orphanage. This is because the location of the orphanage is on the side of the main road towards Pucang Gading. The location of the building is also very close to a river where conditions are steep and against landslides. In addition, there is also no cost that can be allocated to pay a monthly garbage fee. A lot of organic waste, such as fruits and vegetables, is household waste that is generated at this orphanage every day. Based on this background, the PKM team plans to provide skills to the residents of the orphanage to make eco-enzyme. Fruit Peels for Utilization of Organic Waste at the Pucang Gading Putri Aisyiyah Orphanage. The program of activities that will be carried out includes education about the impact of accumulated waste on residents of the orphanage and residents around the orphanage, counseling on how to sort and utilize the waste around them, counseling and training on how to make eco-enzymes by utilizing waste organic matter around them. The results of the training show that there is an increase in the knowledge of the orphanage residents regarding the processing of fruit peel waste into eco-enzymes. Students' knowledge about eco-enzymes increases after socialization, this means that students understand and know how to use eco-enzymes. This is in line with previous research that one's knowledge can increase through listening, seeing, and direct practice.